Turkish Russian relations 1600-2024, an analysis based on expert opinions & perceptions - Nasani, Mohamad (Hasan Kalyoncu Üniversitesi / Lisansüstü Eğitim Enstitüsü / Siyaset Bilimi ve Uluslararası İlişkiler Ana Bilim Dalı, 2025)
The research critically analyzes Turkish-Russian relations between 1600 and 2024 on the basis of expert views regarding historical, geopolitical, security, ideological, economic, and contemporary factors influencing the bilateral relationship. A quantitative research method involved a structured survey of 88 respondents, including media professionals, political analysts, and specialists with either direct or indirect exposure to Turkish-Russian relations. The data collected through the survey were used to identify key determinants influencing policy formation and bilateral relations. The findings indicate that geopolitical and national security concerns are perceived as major drivers of the relationship, followed by economic interdependence in trade and energy sectors. Historical legacies, and also ideological trends such as nationalism and religion, are perceived to be moderate drivers. The analysis also reveals that the perceptions are shaped by respondents' nationality, academic background, and cultural exposure. Although the study references theoretical paradigms like realism, liberalism, and constructivism in placing the findings, the focus is primarily on mapping and examining perceptions from experts. The study ends by offering practitioner suggestions for enhancing cooperative endeavors through realistic diplomacy, economic engagement, and strategic balance, thereby furthering the understanding of this complex and dynamic bilateral relationship. The recommendations and practical implications include the development of confidence-building measures, strengthening cooperative economic activities, and promoting exchanges on the cultural and academic levels for strengthening bilateral relations.

Bu araştırma, Türk-Rus ilişkilerini 1600 ile 2024 yılları arasında etkileyen tarihî, jeopolitik, güvenlik, ideolojik, ekonomik ve çağdaş faktörler bağlamında uzman görüşlerine dayanarak eleştirel bir şekilde analiz etmektedir. Nicel bir araştırma yöntemi kapsamında, Türk-Rus ilişkileriyle doğrudan ya da dolaylı temas hâlinde olan medya mensupları, siyasi analistler ve uzmanlardan oluşan 88 katılımcıyla yapılandırılmış bir anket uygulanmıştır. Anket yoluyla toplanan veriler, politika oluşturma sürecini ve ikili ilişkileri etkileyen temel belirleyicileri ortaya koymak amacıyla kullanılmıştır. Elde edilen bulgular, ilişkilerin en önemli itici güçleri olarak jeopolitik ve ulusal güvenlik kaygılarının öne çıktığını; bunu ticaret ve enerji sektörlerindeki ekonomik karşılıklı bağımlılığın izlediğini göstermektedir. Tarihsel miraslar ile milliyetçilik ve din gibi ideolojik eğilimler ise orta düzeyde etkili faktörler olarak değerlendirilmektedir. Analiz ayrıca, algıların katılımcıların milliyeti, akademik geçmişi ve kültürel birikimi doğrultusunda şekillendiğini ortaya koymaktadır. Araştırma, bulgularını yerleştirirken realizm, liberalizm ve inşacılık gibi kuramsal paradigmaları referans alsa da, esas odak uzmanların algılarını haritalandırmak ve incelemek üzerinedir. Çalışma, gerçekçi diplomasi, ekonomik iş birliği ve stratejik denge yoluyla iş birliğini artırmaya yönelik uygulayıcılara yönelik öneriler sunarak bu karmaşık ve dinamik ikili ilişkiye dair anlayışı derinleştirmeyi amaçlamaktadır. Son olarak, öneriler ve pratik sonuçlar arasında güven artırıcı önlemlerin geliştirilmesi, ekonomik iş birliğinin güçlendirilmesi ve kültürel ile akademik düzeyde karşılıklı değişimlerin teşvik edilmesi yer almaktadır. Bu öneriler, Türk-Rus ilişkilerinin daha sağlam temeller üzerinde ilerlemesine katkı sağlamayı hedeflemektedir.
Keywords: Turkish-Russian relations; expert perceptions; geopolitical factors; national security; economic interdependence